Impacts of severity of Covid-19 infection on the morbidity and mortality of surgical patients. (July 2022) - Al Ani, Amer; Tahtamoni, Rafeef; Mohammad, Yara; Al-Ayoubi, Fawzi; Haider, Nadeem; Al-Mashhadi, Ammar
Abstract: Introduction: One of the challenges of surgery on patients with active SARS-CoV-2(severe acute respiratory syndrome coronavirus 2) infection is the increased risk of postoperative morbidity and mortality. Aim: This study will describe and compare the postoperative morbidity and mortality in asymptomatic patients or those with mild infection with those with severe COVID-19 infection undergoing elective or and emergency surgery. Materials and methods: This is a retrospective study of 37 COVID19 patients who had the infection 7 days prior to and 30 days after emergency or elective surgery. Patients were divided to two groups. Group1: the asymptomatic or those with mild infection that is diagnosed just before surgery (14 patients). Group 2: those who were admitted to the hospital because of severe COVID-19 and were operated for COVID-19 related complications (23 patients). Morbidity and mortality of both groups was studied. Results: There was no significant difference in gender between the two groups. There were 5 females (2 in group 1, and 3 in group 2) and 32 males (12 in group 1, and 20 in group 2). Mean age for all patients was 49.8years (38 for group 1 and 57 for group2). Median age for all patients was 50 years (37.5 for group 1 and 57 years for group 2). Sepsis developed in 7 patients (1 patient in group 1 and in 6 patients in group 2). Statistically there was no significant difference in occurrence of sepsis between the two groups. There was a significant difference in the intensive care stay between the two groups (higher in group 2). Four deaths were reported in group 1 and fourteen in group 2. Eighteen out of thirty-seven patients died. Conclusion: Severity of COVID-19 infection will prolong the hospitalization and ICU stay in surgical patients with no significant effect on mortality.